1988
DOI: 10.1128/jb.170.6.2599-2611.1988
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structure mapping and identification of two regulators of capsule synthesis in Escherichia coli K-12

Abstract: Positive and negative regulatory elements involved in the synthesis of colanic acid, the capsular polysaccharide ofEscherichia coli K-12, have been identified previously. RcsB, a positive regulator for transcription of the structural genes of colanic acid synthesis (cps), is a protein of about 26 kilodaltons which probably acts as a multimer. rcsC, which maps close to rcsB at 48 min on the E. coli chromosome, exerts a negative effect on expression of the structural genes and codes for a protein of about 100 ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 37 publications
8
128
1
Order By: Relevance
“…The increase in RcsB-P levels in the rcsC mutant background would be expected to be quite modest since there is no significant induction in the production of colanic acid (our unpublished observations; Brill et al, 1988). Nonetheless, if the increased level of RcsB-P is directly responsible for the observed defect in biofilm formation, we would expect that full activation of the Rcs phosphorelay would have the same phenotype.…”
Section: Mutations In Rcsc and Rcsd Affect Biofilm Formationmentioning
confidence: 91%
“…The increase in RcsB-P levels in the rcsC mutant background would be expected to be quite modest since there is no significant induction in the production of colanic acid (our unpublished observations; Brill et al, 1988). Nonetheless, if the increased level of RcsB-P is directly responsible for the observed defect in biofilm formation, we would expect that full activation of the Rcs phosphorelay would have the same phenotype.…”
Section: Mutations In Rcsc and Rcsd Affect Biofilm Formationmentioning
confidence: 91%
“…When pHR725 was introduced into the rcsC137 mutant SG20803, in which the Rcs system is constitutively activated (Brill et al, 1988), suppression of the Rcs activation was not observed on LB agar containing X-Gal and 0.5 mM IPTG: the blue colony colour did not differ from that of the mutant carrying the vector plasmid pHR718 (data not shown). This suggests that lgt overexpression does not affect the Rcs signal transduction pathway downstream of RcsC.…”
Section: Lipoprotein Mislocalization and Rcs Activationmentioning
confidence: 99%
“…Two sets of genes whose regulation by the Rcs system is well known, both in E. coli and in S. enterica serovar Typhimurium, are colanic acid genes (Brill et al, 1988;Cano et al, 2002), and genes involved in flagella synthesis and in chemotaxis (Cano et al, 2002;Francez-Charlot et al, 2003). Control of flagella and chemotaxis is exercised through the master operon flhDC (Macnab, 1996).…”
Section: S Enterica Serovar Typhimurium Rcsc Mutants With Constitutimentioning
confidence: 99%
“…The Rcs phosphorelay system was initially characterized in Escherichia coli as a two-component positive regulator of colanic acid capsule synthesis encoded by rcsC and rcsB (Brill et al, 1988;Gottesman et al, 1985;Stout & Gottesman, 1990). The sensor protein RcsC, a hybrid histidine kinase, and the transcriptional activator RcsB are the main components of the system, which also includes a second transcriptional activator, RcsA (Stout et al, 1991) and an intermediate phosphotransmitter, YojN (Takeda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%